Analysis of related influencing factors of prognosis and microbiology in patients with peritoneal dialysis-associated peritonitis - Liu Xiao-hua; Liu Gen-yan; Ren Hai-bin; Liu Kang; Wei Ji-fu; Mao Hui-juan (Linchuang shenzangbing zazhi)
ObjectiveTo determine the related factors influencing prognosis and microbiology of patients with peritoneal dialysis-associated peritonitis（PDAP）.MethodsThe basic clinical data， laboratory indicators and outcomes of patients during occurrence of PDAP， who underwent peritoneal dialysis （PD） in our department from January 2017 to June 2021， were analyzed retrospectively. According to the prognosis of PDAP patients， they were divided into three groups： cure group， withdrawal （extubation）group， and relapse （repeat， recurrence or reappearance of peritonitis after treatment） group. The cured group and the relapse group were considered as the technical survival group. The withdrawal group is considered a technical failure group.ResultsA total of 125 peritonitis cases in 79 selected peritoneal dialysis patients included 78 cases in the cured group，20 cases in the relapse group，27 cases in the withdrawal group. Logistic regression analysis indicated that reduced serum iron， initial treatment regimen of non-first-generation cephalosporin plus third-generation cephalosporins were independent risk factors for withdrawal from peritoneal dialysis in patients with peritoneal dialysis（P<0.05）.Subgroup analysis found that patients in failure group had lower water levels than those in the survival group（P<0.05）.Gram-positive organisms remained major cause of PD-related peritonitis（58.65%，61/104）.Methicillin resistance was noted in 21（67.74%） of 31 coagulase negative staphylococcus isolates. Of 23 gram-negative organisms， 82.61% （19） were susceptible to ceftazidime. We observed trends to an increase in the rates of streptococcal infections in patients with gastrointestinal symptoms and an increase of the incidence of infections by CNS in patients without gastrointestinal symptoms（P<0.05）.ConclusionsReduced serum iron， initial treatment regimen of non-first-generation cephalosporin plus third-generation cephalosporins were independent risk factors for withdrawal from peritoneal dialysis in patients with peritoneal dialysis. Gastrointestinal symptoms are associated with different bacterial infections.